PENGARUH EARNING PER SHARE, PRICE EARNING RATIO, DAN BOOK VALUE PER SHARE PADA HARGA SAHAM - Aletheari, Ida Ayu Made; Jati, I Ketut (E-Jurnal Akuntansi, 2016)
This research aims to prove empirically the effect of earning per share, price earning ratio, and book value per share on stock price. The sample of this research is 42 companies from its population which has 61 property sector companies that listed in Indonesia Stock Exchange in 2012-2014. The sampling method is used in this research is non probability sampling with purposive sampling technique with some criterias. The data collection is done with non participant observation and data analysis technique that is used to test the hypothesis is multiple linear regression analysis. Based on the result of the analysis show that earning per share (EPS) positive effect on stock price, price earning ratio (PER) positive effect on stock price, and book value per share (BVS) positive effect on stock price.
Keywords: EPS; PER; BVS; stock price